2011
DOI: 10.1143/jjap.50.07he01
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Amount of Generated Acoustic Cavitation: Investigation of Spatial Distribution of Acoustic Cavitation Generation Using Broadband Integrated Voltage

Abstract: From the beginnings of medical imaging with radioactivity, an account is given of the development in Aberdeen of CT scanners in nuclear medicine, and their clinical value, leading to the present-day gamma-cameras. Early animal work with electron magnetic resonance is described, which developed into a programme towards nuclear magnetic resonance of water in body tissues. The 1974 NMR image of a mouse, using the nuclear medicine experience, led to a quest to build the first clinically useful whole-body MRI. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…For example, Hodnett et al [26,27] apply a band pass filter between 1,5 MHz and 8 MHzto the signal and then define their cavitation index as the root mean square value of the resulting signal. Similarly, Uchida et al [28,29] define the cavitation index as the integral of the spectrum over a band located in the high frequency region (here between 1 MHz and 5 MHz). An alternative method is to integrate the spectrum on a wider band, after eliminating the lines corresponding to the (sub/ultra) harmonics and/or the fundamental [30].…”
Section: Signal Processing Stepsmentioning
confidence: 99%
“…For example, Hodnett et al [26,27] apply a band pass filter between 1,5 MHz and 8 MHzto the signal and then define their cavitation index as the root mean square value of the resulting signal. Similarly, Uchida et al [28,29] define the cavitation index as the integral of the spectrum over a band located in the high frequency region (here between 1 MHz and 5 MHz). An alternative method is to integrate the spectrum on a wider band, after eliminating the lines corresponding to the (sub/ultra) harmonics and/or the fundamental [30].…”
Section: Signal Processing Stepsmentioning
confidence: 99%
“…5,6) Disintegration time has been of interest for quality checks during the manufacturing process. 7) The acoustic amplitudes during tablet monitoring must be less than the inertial cavitation threshold, [8][9][10][11][12] to prevent the formation of free radicals 13) and the deposition of heat. 14,15) In a prior study, it was reported that tablet disintegration is accelerated after rough handling of tablets.…”
mentioning
confidence: 99%
“…We have also investigated some ultrasonic measurements from the perspective of safety in applications. [1][2][3][4][5][6][7][8][9][10][11][12][13] IEC62539 is an international standard that describes methods for the determination of thermal and mechanical indices ðTI; MIÞ related to diagnostic ultrasound. 14) One important property of the hydrophone used in the determination of MI is the active element size.…”
mentioning
confidence: 99%